Modernity and the Challenge of Pluralism: Some Indonesian Lessons - Robert W. Hefner (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
In the tradition of Western social sciences to grow a sense of